Study of fetomaternal outcome in HIV positive pregnant female at a tertiary health center in South Gujarat - Chauhan, Jigisha; Agarwal, Shraddha; Kansal, Riya; Patel, Zarana; Patel, Krunal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Prenatal identification of HIV infected women is crucial for delivery and optimal care to both mother and fetus. Prevention of parent-to-child transmission has been the major tool to identify HIV-infected pregnant women by voluntary counselling and testing for HIV and provide antiretroviral drug prophylaxis to them during delivery and then to their newborn infants. Aim and objective was to study the fetomaternal outcome of HIV Positive antenatal patients. Methods: This was simple descriptive study which was conducted between January 2017 to June 2019 with 18 months follow-up suggestive of 40 patients were having HIV positive among 9015 deliveries. Thorough examination, investigations and treatment given according to NACO guidelines and fetomaternal outcome were noted in all cases. Results: In present study, prevalence of HIV Positive pregnant women was 0.44%. Out of 40 patients, 5 patients were diagnosed with TB. 55% cases were diagnosed with HIV during ANC examination. 22 (55%) patients were having CD4 count >500 and 1 (2.5%) patient having low CD4 count <200. 32 (80%) patients delivered vaginally and 8 (20%) underwent LSCS. 8 (20%) of babies were admitted to NICU, 3 expired and 37 babies tested negative, 3 losses to follow-up and 34 tested negatives at 18months. Conclusions: Mother-to-child transmission is the predominant way children become infected with human immunodeficiency virus worldwide. Good antenatal care and multidisciplinary approach to HIV-infected women can have good pregnancy outcome and early prophylaxis to the baby leads to decreased incidence of disease in the community.